Information, Entropy, and System Dynamics: A Unified Framework Toward an Extended Thermodynamic Principle of Organization Across Physical, Biological, and Computational Systems - Barack Ndenga (Publisher, 2025)
Classical thermodynamics provides a powerful description of energy conservation, irreversibility, and entropy production, but it does not explicitly formalize information as a state-level quantity capable of governing the emergence and persistence of organization. In this article, I present a unified framework linking information, entropy, and system dynamics for a broad class of physical, biological, and computational systems. I argue that organization is not fully captured by entropy alone, and I formalize organization as a dynamical balance between usable information and effective entropy. I introduce (i) operational definitions of usable information and effective entropy that can be adapted across domains, (ii) a general organizational potential describing whether a system tends toward stable structure or toward disorder, and (iii) a dynamical formulation that predicts transitions between organization, dynamic equilibrium, and disorganization. I show how this framework recovers known results from statistical physics and nonequilibrium thermodynamics, while also providing a coherent language for biological maintenance of order and formachine learning dynamics. I conclude with testable predictions and a roadmap for empirical validation.
This work presents a unified theoretical framework linking information, entropy, and system dynamics to explain the emergence, stability, and breakdown of organization in physical and biological systems. The article argues that organization cannot be fully understood through entropy alone and introduces an information-centered perspective to describe self-organization in non-equilibrium systems. By treating information as a fundamental organizing factor, the framework provides a common conceptual language for phenomena observed across physics, biology, andcomplex systems science. This contribution aims to extend thermodynamic reasoning and offer new foundations for understanding organized behavior in natural systems.